Energy, forces & motion - Smith, Alastair, 1964-; Bhachu, Verinder; Henderson, Corinne; Howell, Laura; Kirkby, Joanne; Russell, Ruth (Tulsa, Okla. : EDC, 2001)
Explains the science of energy, forces, and motion.
Includes index.
7.2
3-6
Keywords: Force and energy -- Juvenile literature; Motion -- Juvenile literature; Force and energy; Motion; Force and energy; Motion